1986
DOI: 10.1007/bf01314143
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation between primary and recurrent cytomegalovirus infections

Abstract: Two blocking tests were applied simultaneously to detect antibodies to cytomegalovirus (CMV) in human serum specimens. Two different peroxidase-labelled tracers were prepared from human sera taken either early during a primary CMV infection or late after recurrent infection. Sera of acute primary CMV cases effectively competed with the labelled antibodies of the "early" tracer but a rather weak inhibition was observed with the "late" tracer. Sera of cases with recurrent infection strongly inhibited both tracer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1987
1987
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Probably, affinity maturation of the antibodies or improved recognition of strain-specific epitopes during the first weeks after primary infection (Griffiths et al, 1984;Schmitz et al, 1986) may account for the strain-specificity of anti-LAV NP antibodies. In fact, a patient coming from Sierra Leone with Lassa fever, who had cross-reacting antibodies in early serum samples, developed a strain-specific antibody response to the Josiah strain only 10 weeks after onset of disease (unpublished data).…”
Section: Discussionmentioning
confidence: 97%
“…Probably, affinity maturation of the antibodies or improved recognition of strain-specific epitopes during the first weeks after primary infection (Griffiths et al, 1984;Schmitz et al, 1986) may account for the strain-specificity of anti-LAV NP antibodies. In fact, a patient coming from Sierra Leone with Lassa fever, who had cross-reacting antibodies in early serum samples, developed a strain-specific antibody response to the Josiah strain only 10 weeks after onset of disease (unpublished data).…”
Section: Discussionmentioning
confidence: 97%
“…It would thus be clinically important to be able to differentiate primary maternal CMV from reactivation infection or reinfection. Schmitz et al [1986] described a blocking test using labeled "early" and "late" antibodies to differentiate primary from recurrent CMV infection and O'Neill et al [19881 studied the proportion of antibodies produced against early and late antigen using immunofluorescence and complement fixation methods. The method used by Hedman and Rousseau for rubella would have a clear advantage in that it involves the introduction of a simple step a t the washing stage of a routine CMV IgG ELISA test.…”
Section: Introductionmentioning
confidence: 99%
“…Several procedures have been described to differentiate primary from recurrent infections [27,[47][48][49][50][51]. Using a microneutralization assay, it was found that neutralizing antibodies first appear approximately 15 weeks after acute infection [52], making it possible to identify recent primary infection by the absence of neutralizing antibodies.…”
Section: Serological Advancesmentioning
confidence: 99%